Application of Qur'an Reading Therapy in Psychiatric Nursing Care for Low Self-Esteem Patients - Yudistira Afconneri; Mardiah; Heppi Sasmita; Basmanelly (Journal of Applied Holistic Nursing Science, 2025)
Background: Schizophrenia is a serious mental health problem that requires full attention. One ofhe symptoms of schizophrenia is chronic low self-esteem.Chronic low self-esteem is an aspect that is often associated with mental disorders and the psychological well-being of patients with mental disorders. One of the psychological therapies for patients with low self-esteem can be done with Al-Quran reading therapy, including psychoreligious therapy that can help patients to increase self-esteem, optimism, improve the process of adaptation to others and is able to prevent and cure mental disorders. The study aims to apply the therapeutic intervention of reading the Qur'an in psychiatric nursing care for patients with low self-esteem by helping patients to increase their self-esteem.. Methods: The design of this study is a case report, therapeutic interventions were carried out on 2 participants during six meetings of Al-Quran reading therapy which took place on April 21 - May 10, 2025. Analysis of the nursing process includes assessment, diagnosis, intervention, implementation, nursing evaluation compared to the results of other people's research and theory. Results: nursing care that had been given to the two patients, Mr. H and Mr. A, showed a positive impact in increasing the patients' self-esteem based on Rosenberg Self-Esteem Scale (RSES) namely in patient H from a score of 10 to 18 and patient A's score increased to 16 from a score of 9. Conclusion: an illustration in implementing general therapy for low self-esteem supplemented with Qur'an reading therapy in all patients who experience low self-esteem.